Comparison of Sensory E?ects of Ropivacaine Alone and Ropivacaine Along with Dexamethasone in Adductor Block for Post-Operative Analgesia After Lower Limb Surgeries - K Girish Reddy; M Adithya Reddy; Ram Babu (Academia Anesthesiologica International, 2020)
Background: The present study was undertaken to study the effect of adding dexamethasone to 0.2% ropivacaine in the adductor canal block. Subjects and Methods: 52 patients for lower limb surgery were divided into 2 groups. Group R received 20 ml of 0.2% ropivacaine + 2 ml   of normal saline and group RD received 20ml of 0.2% ropivacaine with 8 mg of 2 ml dexamethasone. The patient was evaluated for the onset of sensory block and duration of analgesia, side effects and complications. Results: The average age was 61.23   8.16 years in the R group   and 61.77   7.55 years in RD group. The average body weight 64.63   7.08 kg in the R group and 66.9   6.77 kg in RD group. Both groups     had predominantly male patients. There was no significant difference between the 2 groups in terms of ASA grading (P=1.000). The onset of sensory block in group R was 12  1.70 min whereas in group RD it was 11.53   1.66 min, which was not statistically significant (P > 0.05).   The duration of analgesia in group R was 507.96 149.32 min whereas in group RD it was 1082.63 195.11 min, which was statistically highly significant (P<0.0001). Conclusion: The Addition of dexamethasone to 0.2% ropivacaine for the adductor canal block increases the duration of analgesia significantly. But there was no difference in the onset of analgesia.